EFEKTIVITAS PENERAPAN MEDIA VISUAL GAMBAR DALAM MENINGKATKAN HASIL BELAJAR SISWA SMKN 1 RASAU JAYA - Suhardi T, Suhardi T; Mashudi, Mashudi; Noor, Agus Sastrawan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine differences in student learning outcomes by applying visual media images. Research in the form of pre-experimental design with one group pre-test post-test design. The subjects in this study were 36 students of class X TBSM 1 Rasau Jaya. Data collection techniques used are direct observation techniques, direct communication techniques, measurement techniques, and documentary study techniques. Data collection tools observation guidelines, interview guidelines and test results in the form of pre-test and post-test questions. Based on data analysis, the results of the normality test stated that the results of the residual value were normally distributed with a significant value of 0.591> 0.05. While the results of the hypothesis test stated Ho was rejected and Ha was accepted based on the sig value. (2-tailed) in the pre-test and post-test values with a value of 0,000, which is smaller than 0.05. From testing the hypothesis stated that there are differences in student learning outcomes after the application of visual media with an average pre-test value of 53.47 and post-test of 80.13. So with the application of visual media this image there is an increase in student learning outcomes in class X TBSM SMKN 1 Rasau Jaya Kubu Raya Regency.Keywords: Historical Subjects, Learning Outcomes, Visual Media